1978
DOI: 10.1128/iai.19.2.470-476.1978
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of antibody response by group A streptococcal pyrogenic exotoxin and characterization of the cells involved

Abstract: The effect of purified streptococcal pyrogenic exotoxins (SPE) on the antibody response to sheep erythrocytes was studied in cultures of mouse spleen cells. Purified SPE types A, B, and C shared the ability to suppress the day 4 direct plaque-forming cell response when added to cultures. SPE A and C were most suppressive at concentrations of 0.1 to 1 ng per culture, while SPE B was active at 1 microgram per culture. Pretreatment of mice with SPE A, 3 h before removal of their spleens for culture, also produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…DISCUSSION Exotoxins have been shown to be capable of experimentally modulating the immune response. Some exotoxins, such as staphylococcal and streptococcal pyrogenic exotoxins and staphylococcal enterotoxin B, induce a suppression of the immune response (10,11,34). Other exotoxins such as cholera toxin have been shown to induce suppression or enhancement of the immune response, depending on when the toxin is administered during the immunization schedule (18,22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION Exotoxins have been shown to be capable of experimentally modulating the immune response. Some exotoxins, such as staphylococcal and streptococcal pyrogenic exotoxins and staphylococcal enterotoxin B, induce a suppression of the immune response (10,11,34). Other exotoxins such as cholera toxin have been shown to induce suppression or enhancement of the immune response, depending on when the toxin is administered during the immunization schedule (18,22).…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcal enterotoxin B and pyrogenic exotoxin as well as streptococcal pyrogenic exotoxin have been shown to modulate the immune response in mice. The effects of these toxins appear to be generated through T-cells (10,11,25,34). Preliminary studies with Pseudomonas exotoxin A indicated that this toxin may also have a modulatory effect on the murine immune response (0.…”
mentioning
confidence: 99%
“…SpeA was first reported to reduce immunoglobulin production almost 50 years ago; a reduction in immunoglobulin‐secreting B cells was accompanied by a paradoxical increase in spleen weight and 100% expansion in total number of cells in rabbits exposed to SpeA . Notwithstanding the recognized poor sensitivity of murine cells to superantigens, both SpeA and SpeC were shown in older reports to suppress murine spleen B cell IgM responses in a manner that required altered activity of T cells, raising the possibility of either reduced T helper cell function or an increase in T suppressor activity . While superantigen‐induced T cell‐derived secreted products were reported by some to suppress immunoglobulin‐secreting cells , others have reported contact‐dependent T cell‐induced Fas (CD95)‐dependent B cell apoptosis following superantigen exposure in human peripheral blood mononuclear cells, although in our study we did not investigate Fas (CD95)–Fas ligand (CD95L) interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The staphylococcal PE has not been tested for immunosuppressive and immunoenhancing capabilities which were reported for the streptococcal PE (13,20,21). Also, the percentage of S. aureus strains producing the PE has not been determined.…”
Section: Downloaded Frommentioning
confidence: 99%